2008
DOI: 10.1007/bf03346370
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of[111In-DTPA0] octreotide scintigraphy in a family with von Hippel-Lindau disease

Abstract: The identification of patients with von Hippel-Lindau (VHL) disease dictates accurate genetic counseling of family members, whereas screening for early detection of visceral and neurological involvement is usually performed by a combination of radiological and nuclear medicine techniques such as ultrasonography or contrast-enhanced computed tomography of the upper abdomen, magnetic resonance imaging of the central nervous system and 131I-metaiodobenzylguanidine-scintigraphy. The role of 111-indium-diethylenetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 34 publications
(41 reference statements)
0
6
0
Order By: Relevance
“…The frequency of PPGL among participants with vHL type 2 was 60.0% (95% CI = 53.4–66.3%), with moderate heterogeneity being observed ( I 2 = 54.6%) ( 16 , 17 , 21 , 25 , 26 , 28 , 29 , 35 , 36 , 40 , 44 , 45 , 47 , 48 , 53 , 55 , 56 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 ) ( Table 1 ). We observed lower heterogeneity in subgroup analyses restricted to convenience sampling ( I 2 = 25.6%) and to patients whose diagnosis was performed only clinically ( I 2 = 23.1%) (Supplementary Table 7).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The frequency of PPGL among participants with vHL type 2 was 60.0% (95% CI = 53.4–66.3%), with moderate heterogeneity being observed ( I 2 = 54.6%) ( 16 , 17 , 21 , 25 , 26 , 28 , 29 , 35 , 36 , 40 , 44 , 45 , 47 , 48 , 53 , 55 , 56 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 ) ( Table 1 ). We observed lower heterogeneity in subgroup analyses restricted to convenience sampling ( I 2 = 25.6%) and to patients whose diagnosis was performed only clinically ( I 2 = 23.1%) (Supplementary Table 7).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 52 studies, assessing 840 participants with vHL type 2, provided information on the frequency of PPGL. Most of these studies were conducted in Europe ( n =18) ( 16 , 17 , 21 , 25 , 26 , 28 , 29 , 62 , 66 , 68 , 70 , 71 , 72 , 73 , 76 , 83 , 91 , 92 ), followed by Eastern Asia ( n =17) ( 35 , 36 , 40 , 44 , 45 , 47 , 48 , 74 , 75 , 77 , 78 , 79 , 80 , 81 , 82 , 86 , 87 ) and North America ( n =9) ( 53 , 59 , 60 , 61 , 63 , 64 , 65 , 69 , 84 ). All studies assessed patients of all age groups, with the mean onset age of PPGL being 28.8 years (as reported in 21 studies ( 21 , 26 , 35 , 40 , 44 , 47 , 55 , 59 , 60 , 61 , 65 , 67 , 71 , 72 , 74 , 77 , 79 , 85 , 86 , …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…He was re-operated. Pulcrano et al (5) reported the findings of In-111-DTPA0-octreotide scintigraphy in three members of a family with VHLS. The authors concluded that scintigraphy might be useful in the management plan of those patients.…”
Section: Literature Review and Discussionmentioning
confidence: 99%